KEBAHAGIAAN LANSIA ETNIS TIONGHOA: TINJAUAN FENOMENOLOGIS DI PANTI WREDA MERBABU SALATIGA - Violeni Sugianto; Emmanuel Satyo Yuwono (Journal of Innovation Research and Knowledge, 2024)
The population of elderly people (elders) in Indonesia is increasing every year. In 2021, there will be more or less than 7.699 elderly people living in shelters or nursing homes in Central Java. Elderly people who live in shelters or nursing homes certainly come from various ethnicities, including the Chinese ethnic group. The phenomenon found was that Chinese ethnic elders living in nursing homes felt happiness, which was shown by being free from various kinds of mental burdens because their life needs were met. This research aims to look at the happiness experiences of Chinese ethnic elders living in the Merbabu Salatiga nursing home. This research uses qualitative research with phenomenological methods. Data was taken through interviews and observation of two Chinese ethnic elders living in a nursing home. The result of the research found that four themes describe the happiness of Chinese ethnic elderly living in the Merbabu Salatiga nursing home, namely: gratitude is part of happiness, social support brings happiness, adaptation creates happiness, and success builds happiness